Desarrollo de un panel demostrativo para la enseñanza de programación de sensores y actuadores orientados a la robótica educativa. - Heredia Yépez, Adonis Oswaldo (2024)
This research aimed to build a demonstrative panel for teaching the programming of sensors and actuators oriented to educational robotics, which serves as a tool to enhance the teaching-learning process of programming. For its development, applied research based on technological development was used, which allowed the highlighting of the most representative aspects of the desired programming system and its correct technological application. Different elements such as PIR and ultrasonic sensors, stepper and servo motors, Arduino board, and connection elements were used. As a result, a demonstration panel was successfully obtained, which works properly and can be used academically to develop four experimental practices, each with their respective guides, allowing the proper use of the panel for teaching purposes. It is essential to highlight that the same panel created is a tool that can be used by teachers in the same area for teaching programming.